Kiai Pesantren Leadership in Internalizing the Independence Attitude of Students - Said Harismansyah; Nina Nurmila; Irawan Irawan; Bambang Samsul Arifin (Green Publisher Indonesia, 2023)
Background: Indonesia is one of the countries that is prone to earthquakes, especially tectonic earthquakes, because of its geographical location between three large plates. As an Indonesian society, studying natural phenomena from an early age is very important. Therefore, the involvement of educated young people is needed to minimize the impact of earthquakes. Stacked (Stacko for Education) is present as a learning medium for earthquake disaster preparedness based on card games derived from paper waste. The Uno card comes from recycled paper. After that, paper is used to print cards containing questions about earthquake disaster preparedness. Purpose: The purpose of this study is to identify and analyze programs, program implementation, elaborate on internalization and contribution, leadership impact, program evaluation and supporting and inhibiting factors of kiai pesantren efforts in internalizing the independence attitude of students. Method: The approach chosen in this study is a qualitative approach with analytical descriptive methods. Results: shows that: First, the kiai leadership program consists of learning programs, training programs and practice in the field. Second, the implementation of the program is carried out by providing exemplary attitudes, providing motivation, and instilling positive behaviors, especially in the individuals of students. Third, internalization and contribution of kiai leadership by adhering to the values of honesty through, candid and objective speech impacts the attitudes and behaviors of saritri to be honest not manipulative, especially in entrepreneurship. Fourth, the impact is the growth of the spirit of independence of students through the management process of pesantren education to foster and realize the independence attitude and entrepreneurial skills of students. Fifth, program evaluation is carried out through non-attitude scale tests. Sixth, Inhibiting factors, there is a public view that pesantren are not to give birth to entrepreneurs but to produce scholars, the lack of resources (human and natural), equipment, raw materials and capital / finance pesantren, lack of partnership institutions and business capital pesantren. And the supporting factors, there are: support of facilities and infrastructure; support from kiai and ustadz for their students to become independent students; through education and training; The learning process from the pesantren experience that began with direct practical activities in the field students also wanted to follow in the footsteps of the founder kiai. Conclusion: Pesantren as an education provider has advantages compared to other educational institutions.